Jawapan

2016-03-02T13:13:18+08:00
M - 6p = 10----(1)
3m + 4p = 8----(2)

(1) darab 3;
3m - 18p = 30---(3)

(3) tolak (2);
(3m -18p) - (3m + 4p) = 30 - 8
3m - 18p - 3m - 4p = 22
-22p = 22
p = 22 bahagi (-22)
p = -1

p = -1 digantikan ke dalam (1);
m - 6p = 10
m - 6(-1) = 10
m + 6 = 10
m = 10 - 6
m = 4

maka, p = -1 dan m = 4
2016-03-02T18:05:12+08:00
M-6p=10 ------(1)
3m+4p=8 -------(2)

dari (1)
m=10+6p -------(3)

ambik (2) masukkan (3)
[nilai p]
3m+4p=8
3(10+6p)+4p=8
30+18p+4p=8
30+22p=8
22p=8-30
22p= -22
p= -22/22
p= -1

[nilai m]
ambik (3)
m=10+6p
m=10+6(-1)
m=10-6
m=4

maka nilai p= -1 , nilai m=4
1 5 1